Complete callosal agenesis, pontocerebellar hypoplasia, and axonal neuropathy due to AMPD2 loss. (August 2015) - Marsh, Ashley P.L.; Lukic, Vesna; Pope, Kate; Bromhead, Catherine; Tankard, Rick; Ryan, Monique M.; Yiu, Eppie M.; Sim, Joe C.H.; Delatycki, Martin B.; Amor, David J.; McGillivray, George; Sherr, Elliott H.; et al.
Abstract : Objective: To determine the molecular basis of a severe neurologic disorder in a large consanguineous family with complete agenesis of the corpus callosum (ACC), pontocerebellar hypoplasia (PCH), and peripheral axonal neuropathy. Methods: Assessment included clinical evaluation, neuroimaging, and nerve conduction studies (NCSs). Linkage analysis used genotypes from 7 family members, and the exome of 3 affected siblings was sequenced. Molecular analyses used Sanger sequencing to perform segregation studies and cohort analysis and Western blot of patient-derived cells. Results: Affected family members presented with postnatal microcephaly and profound developmental delay, with early death in 3. Neuroimaging, including a fetal MRI at 30 weeks, showed complete ACC and PCH. Clinical evaluation showed areflexia, and NCSs revealed a severe axonal neuropathy in the 2 individuals available for electrophysiologic study. A novel homozygous stopgain mutation in adenosine monophosphate deaminase 2 ( AMPD2 ) was identified within the linkage region on chromosome 1. Molecular analyses confirmed that the mutation segregated with disease and resulted in the loss of AMPD2. Subsequent screening of a cohort of 42 unrelated individuals with related imaging phenotypes did not reveal additional AMPD2 mutations. Conclusions: We describe a family with a novel stopgain mutation in AMPD2 . We expand the phenotype recently described as PCH type 9 to include progressive postnatal microcephaly, complete ACC, and peripheral axonal neuropathy. Screening of additional individuals with related imaging phenotypes failed to identify mutations in AMPD2, suggesting that AMPD2 mutations are not a common cause of combined callosal and pontocerebellar defects.